3q^2+16=-19q

Simple and best practice solution for 3q^2+16=-19q equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3q^2+16=-19q equation:


Simplifying
3q2 + 16 = -19q

Reorder the terms:
16 + 3q2 = -19q

Solving
16 + 3q2 = -19q

Solving for variable 'q'.

Reorder the terms:
16 + 19q + 3q2 = -19q + 19q

Combine like terms: -19q + 19q = 0
16 + 19q + 3q2 = 0

Factor a trinomial.
(16 + 3q)(1 + q) = 0

Subproblem 1

Set the factor '(16 + 3q)' equal to zero and attempt to solve: Simplifying 16 + 3q = 0 Solving 16 + 3q = 0 Move all terms containing q to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + 3q = 0 + -16 Combine like terms: 16 + -16 = 0 0 + 3q = 0 + -16 3q = 0 + -16 Combine like terms: 0 + -16 = -16 3q = -16 Divide each side by '3'. q = -5.333333333 Simplifying q = -5.333333333

Subproblem 2

Set the factor '(1 + q)' equal to zero and attempt to solve: Simplifying 1 + q = 0 Solving 1 + q = 0 Move all terms containing q to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + q = 0 + -1 Combine like terms: 1 + -1 = 0 0 + q = 0 + -1 q = 0 + -1 Combine like terms: 0 + -1 = -1 q = -1 Simplifying q = -1

Solution

q = {-5.333333333, -1}

You can always share this solution

See similar equations:

| (-2x^2+3y^3)+(6x-5)=0 | | 2x^2+6x+4=0 | | 2x^2-5x-75=0 | | 2x^2-10x+18=0 | | 9s^2+3s-20=x | | (x-1)(x^2-4)+2(x-1)(x+2)=(x-1)P | | 9x^2-4.5x-3.5=0 | | 6x^2-5x-14=0 | | x^4-7x-18=0 | | x^2-8x+18=0 | | x^2-8b+18=0 | | 30a^2+am-m^2=0 | | 30a^2+am-m^2=o | | 12s^2+11st-5t^2=0 | | 14x^2+11yx-15y^2=0 | | 3x^2+8=0 | | -2v^2-v+12=-3v^2+6v | | x^2+15x-64=0 | | 2x^2+8x-2=0 | | 12x^2-x-20=0 | | 5x^2+13x+6=0 | | x^3-12x^2+35x=0 | | x^3-13x^2+30x=0 | | 6x^2+17x-45=0 | | x^4-3x^2+1=0 | | 5x^2-5x-3= | | 3x^2-13x+14=0 | | 6x^2+x-c=(cx-1)(3x+2) | | X*x=x^2 | | 9c=c^2 | | 3x^2-12=0 | | 3x^2-8=0 |

Equations solver categories